How to Make a Cost Model for the Birth Cohort Biobank in China - Wu, Meiqin; Wu, Deqing; Hu, Chunping; Yan, Chonghuai (Frontiers in Public Health, 2020)
Biobanks and cohort studies are a popular topic in China these days and even in the global scientific research field. Cohorts with biological material are necessary to investigate potential biological mechanisms behind a disease and its early detection. Establishing a biobank is expensive and the long-term sustainability of biorepositories is a key issue globally. There is some published information on tools to calculate the biospecimen user fee; however, they may not be suitable for China’s biobanks (as most of the biobanks in China are not-for-profit and are funded by government or research grants, and as such, funding is a major constraint). The limited published data also tend to be highly variable and specific to the type of biobank. The authors of this article aim to present the basis of a cost analysis model for a biobank of human biological samples of a birth cohort in Shanghai, China. And the findings are potentially of interest to biobankers in adopting new perspectives when considering potential collaborators.